Characteristics of Responsibilities in Tamansiswa Middle School Students, Curup Tengah District: Implementation and Strategy - Deri Wanto (IAIN Ambon, 2022)
This responsibility is the attitude and behavior of a person in carrying out their duties and obligations as they should be done to themselves, the community, the environment, the state and to Allah SWT, in the sense that students can be said to be responsible if they have carried out their duties and obligations such as following the process. learning well in the classroom, coming to class on time, wearing school uniforms and paying tuition on time. This study aims to determine the strategy of Islamic religious education teachers in instilling the character of responsibility in the learning process at Tamansiswa Junior High School, Central Curup District. This type of research is descriptive qualitative, using data collection techniques including observation, interviews, and documentation. The results of this study indicate that first, the condition of the character of responsibility in Tamansiswa Junior High School, Central Curup District, namely following the learning process well in class, entering class on time, wearing uniforms according to the rules and paying tuition on time. The two strategies that can be carried out by teachers in instilling the character of responsibility in students at Tamansiswa Junior High School, Curup District are by using various character education strategies and giving different tasks to each student and grouping students based on their abilities.